2015
DOI: 10.1038/nature16057
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibody–antibiotic conjugate eliminates intracellular S. aureus

Abstract: Staphylococcus aureus is considered to be an extracellular pathogen. However, survival of S. aureus within host cells may provide a reservoir relatively protected from antibiotics, thus enabling long-term colonization of the host and explaining clinical failures and relapses after antibiotic therapy. Here we confirm that intracellular reservoirs of S. aureus in mice comprise a virulent subset of bacteria that can establish infection even in the presence of vancomycin, and we introduce a novel therapeutic that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
693
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 682 publications
(760 citation statements)
references
References 44 publications
10
693
0
3
Order By: Relevance
“…These points were resolved in the studies described here, as evidenced from the drug stability characteristics, and the high potencies and specificities of the ADCs containing quaternary ammonium linkers. Recently, in parallel with our ADC efforts, a val-cit-dipeptide-based quaternary ammonium linker was reported for the conjugation of a rifalogue antibiotic for an antibody-antibiotic conjugate (AAC) approach to treat intracellular methicillin-resistant S. aureus (28). Taken together, these results underscore the applicability of this approach for targeted drug delivery.…”
Section: Discussionmentioning
confidence: 58%
“…These points were resolved in the studies described here, as evidenced from the drug stability characteristics, and the high potencies and specificities of the ADCs containing quaternary ammonium linkers. Recently, in parallel with our ADC efforts, a val-cit-dipeptide-based quaternary ammonium linker was reported for the conjugation of a rifalogue antibiotic for an antibody-antibiotic conjugate (AAC) approach to treat intracellular methicillin-resistant S. aureus (28). Taken together, these results underscore the applicability of this approach for targeted drug delivery.…”
Section: Discussionmentioning
confidence: 58%
“…These findings can help guide the design of future ADCs for maximal efficacy and optimal therapeutic window. Beyond ADCs, our results may also be instructive for the development of emerging therapeutics that are dependent on cleavage technologies, such as antibody-antibiotics conjugates (37,38). Understanding how protease-cleavable linkers operate can help better design and anticipate challenges for these types of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…proposed a novel therapeutic using antibody-antibiotic conjugates to clear intracellular reservoirs of Staphylococcus aureus. 24 Similar strategies could also be used to eliminate persistent maternal GBS colonization and to potentially reduce the risk of neonatal infection. A previous study reported that serotype Ib GBS treated with sub-inhibitory concentrations of b-lactam antibiotics, including penicillin, increased killing of GBS by phagocytes.…”
Section: Cps Type Percent Survivalmentioning
confidence: 99%